Factors Impacting Postoperative Opioid Use Among Patients Undergoing Implantation of Inflatable Penile Prosthesis. Issue 11 (12th October 2021) - Ehlers, Mark E.; Mohan, Charan S.; Akerman, Jason P.; McGowan, Micah; McCormick, Benjamin J.; Hacker, Kathryn E.; Coward, R. Matthew; Figler, Bradley D.
ABSTRACT: Background: While there is an increasing burden of chronic postoperative opioid use and opioid abuse in the United States, opioid use following inflatable penile prosthesis (IPP) surgery has not been well described. Aim: Describe postoperative opioid use following IPP surgery. Methods: Seventy-four consecutive patients undergoing IPP implantation by a single surgeon were enrolled. Self-reported diaries tracked the type and amount of medication taken for 2 weeks following IPP surgery. High opioid consumers were defined as those consuming more than the median amount (10 mg) of opioids during the first 2 weeks postoperatively. Multivariate analyses were performed using stepwise backward elimination. Outcomes: Quantification of opioid use postoperatively and factors related to high opioid use. RESULTS: Fifty-six patients were included after 7 were excluded for preoperative opioid use and 11 were excluded for inability to contact. Median age was 67.5. Devices used were Boston Scientific (41, 73%) and Coloplast (15, 27%). All patients received local anesthetic. Most surgeries (44, 79%) were performed as outpatient. Preoperative analgesia with acetaminophen, celecoxib, and pregabalin was administered in 44 (78%), 44 (78%), and 28 (50%) of cases respectively; 32 (57%) of patients received 2 medications, 21 (36%) received three medications. In hospital median morphine equivalents was 7.5 (interquartile range [IQR] 0–7.5). Oxycodone prescribed at discharge was 50 mg (29, 52%), 75 mg (4; 7%), and 100 mg (23; 41%). Median milligrams of oxycodone used was 10 mg (IQR 0–23.5) at 7 days and 10 (IQR 0–37.5) at 14 days postdischarge. On univariate analysis, factors associated with an increased likelihood of high opioid use were morphine equivalents utilized in hospital (odds ratio [OR] 1.13, P < .05) and milligrams oxycodone prescribed at discharge (OR 1.05, P < .001) while patient demographics, procedure characteristics, and analgesic types were not found to be predictive of high opioid use. On multivariate analysis, milligrams oxycodone prescribed at discharge (OR 1.04, P < .005) were associated with an increased likelihood of high opioid use after discharge. Clinical Implications: Increased understanding of opioid use after IPP surgery may improve prescribing patterns after discharge. Strengths & Limitations: This study quantified post discharge opioid use over the first 14 postoperative days. It is limited by single surgeon, small sample size, and retrospective design. CONCLUSION: Provider opioid prescribing patterns were associated with high opioid consumption postoperatively and a substantial amount of opioids prescribed at discharge remain unused by patients, suggesting that we can reduce or replace the amount of opioids that are prescribed.